Pengaruh Motivasi, Kompetensi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Sekretariat Daerah Kabupaten Karawang - Dewany, Arum; Hersona GW, Sonny; Hendriyani, Rina Maria (Community Engagement and Emergence Journal (CEEJ), 2025)
Employee performance is a crucial factor that determines the effectiveness of governmental organizations in achieving their objectives and delivering optimal public services. At the Regional Secretariat of Karawang Regency, employee performance is influenced by motivation, competence, and the work environment. This study aims to analyze the influence of these three variables on employee performance, both partially and simultaneously. Employing a quantitative approach with a descriptive-verificative method, the study involved 96 respondents from a total population of 126 employees selected through random sampling. Data were collected using questionnaires and analyzed using path analysis with the assistance of SPSS software. The descriptive results indicate that motivation (394.8), competence (382.8), work environment (392.3), and employee performance (337.7) fall within the “Agree” category, demonstrating that motivation, competence, and the work environment are in good condition and effectively support employee performance. Partially, motivation contributes 10.11% to employee performance, competence contributes 6.73%, and the work environment contributes 6.85%. Simultaneously, the three variables collectively contribute 23.70% to employee performance, while the remaining 76.30% is influenced by other factors such as leadership, organizational culture, and reward systems. Keywords: motivation, competence, work environment, employee performance.